Mineral composition and its relations to readily available element concentrations in cultivated soils of Finland - Riikka Keskinen; Stephen Hillier; Eero Liski; Visa Nuutinen; Mercy Nyambura; Mia Tiljander (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2022)
Mineral composition is a fundamental feature that affects the properties and functions of soil through physical, chemical and biological interactions. However, comprehensive knowledge on the mineralogy of agricultural topsoils of Finland has been lacking. In this study, the mineral composition of 120 soil samples included in the national monitoring of agricultural soils of Finland was determined using state-of-the-art quantitative x-ray diffraction analysis by a prior measured full pattern fitting methodology. Quartz, plagioclase and K-feldspar were found to be the dominant soil mineral components. Amphiboles and micas were also common, and several other mineral phases were detected in small quantities. The relative proportions of quartz and plagioclases increased and those of mica, goethite, disordered clay minerals, kaolin and amorphous inorganic components decreased as the soil particle size increased. Compositional statistical analysis discerned a positive association between the prevalence of 12 elements and organic matter and surface-active minerals (goethite, chlorite, disordered clays, kaolin and inorganic amorphous materials), whereas micas contributed to the prevalence of K. The present data agreed with general conceptions of Finnish soil mineralogy but revealed novel details in the mineral composition. The relationship observed between soil textural and mineral compositions supports the current texture-based soil classification system and recommendations.